2022
DOI: 10.1155/2022/5841978
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Optimized Emergency Care on Treatment Rate and Prognosis of Elderly Patients with Acute Stroke in Emergency Department: A Systematic Review and Meta-Analysis

Abstract: Objective. This research was to detect the treatment rate and prognosis of elderly patients with acute stroke in emergency department by the optimization of emergency care applying meta-analysis. Methods. The online databases including PubMed, EMBASE, ScienceDirect, Cochrane Library, China knowledge Network Database (CNKI), China VIP Database, Wanfang Database, and China Biomedical Literature Database (CBM) were searched. The retrieval time limit was set from the establishment of the database to the present. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…According to the previous study [ 15 ], the standardized mean difference (SMD) with Hedges' g was chosen as the measure of the effect. The effect size was calculated using a random-effect model with a restricted maximum-likelihood (REML) and considered a large, moderate, and small effect with respect to the SMD values of 0.8, 0.5, and 0.2, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…According to the previous study [ 15 ], the standardized mean difference (SMD) with Hedges' g was chosen as the measure of the effect. The effect size was calculated using a random-effect model with a restricted maximum-likelihood (REML) and considered a large, moderate, and small effect with respect to the SMD values of 0.8, 0.5, and 0.2, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Emergency departments (EDs) are critical high-stake environments within the healthcare system [1], where the pace is relentless and the margin for error is minimal [2,3]. Tese units serve as the central hub for acute treatment, where decisions must be rapid and precise [4][5][6], with the potential to signifcantly alter patient outcomes [3].…”
Section: Introductionmentioning
confidence: 99%
“…Emergency departments (EDs) are critical high-stake environments within the healthcare system [1], where the pace is relentless and the margin for error is minimal [2,3]. Tese units serve as the central hub for acute treatment, where decisions must be rapid and precise [4][5][6], with the potential to signifcantly alter patient outcomes [3]. Te intensity and pressure inherent in emergency departments require a leadership style that not only facilitates rapid decision-making but also nurtures a supportive and cohesive team environment [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%